Evaluation of using veliger stage larvae for the preparation of metaphase spreads from the pacific abalone (Haliotis discus hannai) - Jae Hoon Choi; Eun Jeong Kim; Choul-Ji Park; Yoon Kwon Nam; Seung Pyo Gong (The Korean Society of Animal Reproduction and Biotechnology, 2020)
Karyotype analysis is a major work in the process of triploid abalone production for the purpose of productivity and quality improvement. However, the metaphase spreads for karyotype analysis have been prepared just from the larvae at trochophore stage, which has restricted the spectrum of sample correction inhibiting more efficient analysis. Here, we investigated the feasibility of preparing metaphase spreads from the larvae at veliger stage that is the next developmental stage of trochophore. For this, diploid and triploid larvae at trochophore and veliger stages from Pacific abalone (Haliotis discus hannai) were subjected to metaphase spread preparation and its efficiencies were measured and compared each other. As the results, although the efficiencies of metaphase spread preparation were significantly lower in the larvae at veliger stage compared to the ones at trochophore stage regardless of ploidy status, we found that the preparation of metaphase spreads, which showed the clear chromosomal images containing the normal number of chromosomes, was possible from the veliger stage larvae. On the other hands, all larvae used in this study regardless of developmental stage and ploidy did not show colchicine sensitivity. Moreover, no significant difference was observed in cell cycle distribution of the cells comprising larvae between two developmental stages regardless of ploidy status. These suggested that the details of protocol to prepare metaphase spreads from abalone larvae should be optimized depending on its developmental stages. Taken together, we demonstrated the feasibility of preparing metaphase spreads from H. discus hannai veliger stage larvae for karyotype analysis.